Continuous production method of carbon nanotubes
The continuous gas phase synthesis method addresses the challenge of uniform diameter control and yield in carbon nanotube production by using a controlled liquid phase mixture and reactor introduction, enhancing the quality and efficiency of carbon nanotube manufacturing.
Patent Information
- Application Number
- JP2023527714
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-09
- Filing Date
- 2021-10-14
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-10-14
AI Technical Summary
Conventional methods for producing carbon nanotubes struggle with uniform control of diameter and low production yield, making it difficult to achieve consistent quality and efficiency.
A continuous gas phase synthesis method involving a liquid phase mixture formation step with specific ratios of solvent, metal salt, surfactant, reducing agent, and performance enhancer, followed by introduction into a heated reactor with a carrier gas to form carbon nanotubes.
Enables uniform control of carbon nanotube diameter and increases production yield, resulting in improved consistency and efficiency of carbon nanotube synthesis.
Smart Images

Figure 0007613654000001 
Figure 0007613654000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for continuously producing carbon nanotubes using a gas phase synthesis method, and more particularly to a method for continuously producing carbon nanotubes by producing catalytic metal nanoparticles of uniform size and reacting them with a carbon source in the gas phase to continuously produce carbon nanotubes. [Background technology]
[0002] Thermoplastic resins, especially high-performance plastics with excellent mechanical properties and heat resistance, are used in various applications. Depending on the field of application, such high-performance plastics are required to have antistatic properties such as antistatic and dust contamination to prevent malfunction and contamination of parts, and electrical conductivity is required in addition to the existing physical properties.
[0003] In order to impart such electrical conductivity to high-performance plastics, surfactants, metal powders, metal fibers, etc. have been added in the past, but these ingredients have problems such as low electrical conductivity or reducing physical properties, such as weakening mechanical strength, etc. For this reason, there is growing interest in carbon materials with electrical conductivity.
[0004] Conductive carbon black is generally used as a carbon material with electrical conductivity. However, in order to achieve high electrical conductivity using conductive carbon black, a large amount of carbon black must be added, and the carbon black structure may decompose during the melt mixing process, which may result in poor processability of the resin and a significant decrease in thermal stability and physical properties. Therefore, in order to improve electrical conductivity while reducing the amount of conductive filler added, active research is being conducted on carbon nanotube-resin composites that add carbon nanotubes instead of conductive carbon black.
[0005] Carbon nanotubes are a substance discovered in Japan in 1991. They consist of one carbon atom bonded to three adjacent carbon atoms, with the bonds between these carbon atoms forming hexagonal rings, and these rings are repeated in a honeycomb pattern, with the planes rolled up to form a cylindrical tube.
[0006] Carbon nanotubes are classified into single-walled carbon nanotubes (SW carbon nanotubes) with a diameter of about 1 nm, which are made up of a single layer, double-walled carbon nanotubes (DW carbon nanotubes) with two layers, and multiwalled carbon nanotubes (MW carbon nanotubes) with a diameter of about 5 to 100 nm, which are made up of three or more layers.
[0007] Such carbon nanotubes can be synthesized by various methods such as arc discharge, laser evaporation, thermal chemical vapor deposition (CVD), catalytic synthesis, and plasma synthesis. These methods synthesize carbon nanotubes at high temperatures ranging from several hundred to several thousand degrees or are performed under vacuum.
[0008] However, conventional methods have problems in that it is difficult to form catalysts of uniform size, and therefore difficult to uniformly control the diameter of the carbon nanotubes produced. In addition, the production yield of carbon nanotubes is reduced due to the production of by-products such as carbon. There is a need for a new method for producing carbon nanotubes that can solve these problems. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a continuous method for producing carbon nanotubes using a gas phase synthesis method, which can uniformly control the diameter of carbon nanotubes and increase the production yield of carbon nanotubes. [Means for solving the problem]
[0010] In order to achieve the above object, one embodiment of the present invention provides a continuous method for producing carbon nanotubes, comprising: a liquid phase mixture formation step of mixing and stirring a solvent, a metal salt, a surfactant, a reducing agent and a functional enhancer to produce an emulsion mixture; a gas phase mixture formation step of mixing the emulsion mixture with a carrier gas to produce a gas phase mixture; and a reaction step of introducing the gas phase mixture into a heated reactor to form carbon nanotubes.
[0011] A carbon source may be further mixed in the gas phase mixture forming step.
[0012] The liquid phase mixture forming step may include a first mixing step of mixing and stirring a solvent, a metal salt and a surfactant, and a second mixing step of adding a reducing agent and a performance enhancer to the mixture obtained through the first mixing step and stirring the mixture.
[0013] The solvent may be at least one selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alcohol compounds, and water.
[0014] The emulsion mixture may contain, relative to 100 parts by weight of the solvent, 0.01 to 5 parts by weight of a metal salt, 5 to 17 parts by weight of a surfactant, 0.02 to 10 parts by weight of a reducing agent, and 0.1 to 0.4 parts by weight of a performance improver.
[0015] The performance enhancer may include at least one of an indole, an imidazole, and a hectorite compound.
[0016] The performance enhancer may be a mixture of at least one first compound selected from the group consisting of indole and imidazole, and a second compound including a hectorite compound. Effect of the Invention
[0017] The method for continuously producing carbon nanotubes of the present invention has the advantage that the diameter of carbon nanotubes can be controlled uniformly and the production yield of carbon nanotubes can be increased. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Before describing in detail preferred embodiments of the present invention below, it will be made clear that the terms and words used in the claims of this specification should not be interpreted limitedly to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical ideas of the present invention.
[0019] Throughout this specification, when a part "comprises" a certain element, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0020] Throughout this specification, "%" used to indicate the concentration of a particular substance means % (w / w) in the case of solid / solid, % (w / vol) in the case of solid / liquid, and % (vol / vol) in the case of liquid / liquid, respectively, unless otherwise specified.
[0021] Generally, a colloid means anything whose particle size is smaller than 0.45 μm (or 0.2 μm) and larger than 1000 Da (Dalton, mass of one molecule), but in the specification of the present invention, a "colloidal solution" means a solution containing particles whose particle size is several to several hundred nanometers, and is sometimes used to include their precursors as well.
[0022] Hereinafter, an embodiment of the present invention will be described. However, the scope of the present invention is not limited to the following preferred embodiment, and a person skilled in the art can implement various modifications of the contents described in this specification within the scope of the present invention.
[0023] First, the present invention relates to a method for continuously producing carbon nanotubes, comprising: a mixture producing step of producing an emulsion mixture by mixing and stirring a solvent, a metal salt, a surfactant, a reducing agent and a performance enhancer; a gas-phase mixture forming step of mixing the emulsion mixture with a carrier gas to form a gas-phase mixture; and a reaction step of introducing the gas-phase mixture into a heated reactor to form carbon nanotubes.
[0024] The mixture preparation step is a step of preparing an emulsion mixture, which is a precursor for forming carbon nanotubes, by mixing a solvent, a metal salt, a surfactant, a reducing agent, and a functional enhancer.
[0025] The metal salt contained in the emulsion mixture functions as a catalyst for forming carbon nanotubes, and through the mixture preparation step, the metal is formed into fine particles with a particle size of 300 nm or less, which has different physical properties and performance from particles with a larger particle size. In particular, the surface area per unit mass increases significantly, improving the function, and physical property changes such as a decrease in the melting point of the particles and discoloration occur.
[0026] In addition, nanometer-sized fine metal particles are highly reactive and can exist in a suspended state in the gas phase, so they can be used as a catalyst for synthesizing carbon nanotubes in the gas phase. The particle size of such metals becomes nanometer-sized by the mixture preparation step, and can be uniformly dispersed in the solvent.
[0027] More specifically, the mixture production step is a step of producing an emulsion mixture containing 0.01 to 5 parts by weight of a metal salt, 5 to 17 parts by weight of a surfactant, 0.02 to 10 parts by weight of a reducing agent, and 0.1 to 0.4 parts by weight of a performance enhancer relative to 100 parts by weight of a solvent.
[0028] The solvent functions as a medium for uniformly dispersing the metal salt, and also functions to provide a carbon source required for the synthesis of carbon nanotubes, if necessary.
[0029] As such a solvent, at least one selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alcohol compounds, and water can be used. As aromatic hydrocarbons, benzene, toluene, xylene, etc. can be used, as aliphatic hydrocarbons, hexane, heptane, octane, etc. can be used, and as alcohol compounds, ethanol, propyl alcohol, polyethylene glycol, etc. can be used, but are not limited thereto.
[0030] As described above, the metal salt functions as a catalyst in the carbon nanotube synthesis reaction, and as such a metal salt, at least one metal salt selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), platinum (Pt), palladium (Pd), molybdenum (Mo), and vanadium (V) can be used, which is at least one metal salt selected from the group consisting of oxides, nitrides, borides, fluorides, bromides, sulfides, chlorides, and carbonates.
[0031] The metal salt may be included in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the solvent. If the content of the metal salt is less than 0.01 parts by weight, the amount of catalyst required for the synthesis of carbon nanotubes is insufficient, resulting in a problem of reduced efficiency in the synthesis of carbon nanotubes, whereas if the content of the metal salt exceeds 5 parts by weight, the carbon nanotubes are not obtained additionally even if the process variables are changed, and instead a large amount of unreacted catalyst is generated, resulting in a problem of reduced purity of the carbon nanotubes. Therefore, it is preferable that the content of the metal salt is within the above weight range.
[0032] The surfactant is added to form the metal salt or metal into nanometer-sized particles, maintain the metal salt or metal in a particulate state until it reacts with the carbon source to form carbon nanotubes, and disperse the fine metal particles uniformly and stably in the solvent.
[0033] As such a surfactant, at least one of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and an amphoteric surfactant can be used.
[0034] As an example, the nonionic surfactant may be polyoxyethylene, alkyl glucoside, alkyl polyglucoside, polyhydroxy fatty acid amide, alkoxylated fatty acid ester, sucrose ester, amine oxide, alcohol ethoxylate, amide ethoxylate, amine oxide, or alkyl glucoside. For example, cocamide methyl, C8-C14 glucose amide, C8-C14 alkyl polyglucoside, sucrose cocoate, sucrose laurate, lauramine oxide, cocoamine oxide, or the like may be used, but is not limited thereto.
[0035] As an example of the anionic surfactant, alkyl sulfates, ethoxylated alkyl sulfates, alkyl ethoxy carboxylates, alkyl glyceryl ether sulfonates, ethoxy ether sulfonates, methyl acyltaurates, alkyl sulfosuccinates, alkyl ethoxy sulfosuccinates, alpha-sulfonated fatty acids, alkyl phosphate esters, ethoxylated alkyl phosphate esters, linear alkyl benzene sulfonates, paraffin sulfonates, alpha-olefin sulfonates, alkyl alkoxy sulfates, and the like can be used, including, but not limited to, sodium lauryl sulfate, sodium laureth sulfate, and sodium coco sulfate.
[0036] As an example, the cationic surfactant may be at least one selected from the group consisting of cetyltrimethylammonium bromide, decyltrimethylammonium bromide, dodecyltrimethylammonium bromide, didecyldimethylammonium bromide, cetyldimethylammonium chloride, lauryldimethylammonium chloride, stearyldimethylammonium chloride, tallow dimethylammonium chloride, ditallow dimethylammonium methyl sulfate, coconut ammonium chloride, stearamidopropyl PG-dimonium chloride phosphate, and stearamidopropyl ethyldimonium ethosulfate, but is not limited thereto.
[0037] Examples of the amphoteric surfactant that can be used include, but are not limited to, alkyl betaines, amido betaines, sulfo betaines, hydroxysulfo betaines, amido sulfo betaines, phospho betaines, imidazolinium betaines, aminopropionic acid surfactants, and amino acid surfactants.
[0038] The surfactant can be used in an amount of 5 to 17 parts by weight per 100 parts by weight of the solvent, and if the surfactant content is less than 5 parts by weight, the metal salt is not sufficiently microparticulated, and the microparticulated metal salt is not uniformly distributed in the solvent but aggregates with each other, making it difficult to synthesize carbon nanotubes of uniform size. On the other hand, if the surfactant content exceeds 17 parts by weight, the effects of additional nanoparticulation of the metal salt and improvement of dispersibility cannot be obtained, and instead the excess surfactant reduces the catalytic function of the metal salt, resulting in a decrease in the yield of carbon nanotubes, so it is preferable to include the surfactant within the above weight range.
[0039] The reducing agent is added to reduce the metal salt to form metal particles having a uniform size, and may be included in an amount of 0.02 to 10 parts by weight per 100 parts by weight of the solvent. If the content of the reducing agent is less than 0.02 parts by weight, the metal salt will not be sufficiently reduced, resulting in non-uniform physical properties of the synthesized carbon nanotubes. If the content of the reducing agent is more than 10 parts by weight, there is a problem that the excess reducing agent will cause a decrease in the physical properties of the emulsion mixture and therefore a decrease in productivity of carbon nanotube synthesis. Therefore, it is preferable to include the reducing agent within the above weight range.
[0040] The reducing agent may be, but is not limited to, an inorganic compound such as hydrazine, LiBH4, or NaBH4, or a compound having a functional group with reducing power such as ethylene oxide.
[0041] The performance enhancer is a component added to increase the phase stability of the colloidal solution by forming metal particles of a uniform and stable size and preventing aggregation of metal particles, and to increase the yield of carbon nanotubes from the metal. Examples of the performance enhancer include at least one of indole, imidazole, and hectorite compounds.
[0042] The performance enhancer may be included in an amount of 0.1 to 0.4 parts by weight per 100 parts by weight of the solvent. If the content of the performance enhancer is less than 0.1 parts by weight, it is difficult to obtain the above-mentioned effects, and if the content of the performance enhancer exceeds 0.4 parts by weight, the stability of the colloidal solution is reduced, resulting in problems such as reduced process efficiency and synthesis efficiency during the subsequent synthesis of carbon nanotubes. Therefore, it is preferable to include the performance enhancer within the above weight range.
[0043] Such performance enhancers include at least one of indole, imidazole and hectorite compounds, and the hectorite compound may be dihydrogenated tallow benzylmonium hectorite, disteardimonium hectorite, quaternium-18 hectorite or stearalkonium hectorite.
[0044] Preferably, at least one first compound selected from the group consisting of indole and imidazole and a second compound which is a hectorite compound can be used together.
[0045] When only the first compound is used, the yield of carbon nanotubes is improved by the metal catalyst, but the first compound reduces the phase stability of the colloidal solution, and metal atoms aggregate with each other during the process of reducing metal ions to metal atoms, resulting in the formation of metal aggregates. Such aggregates make the resulting carbon nanotubes have non-uniform diameters, preventing the synthesis of carbon nanotubes with a uniform and constant diameter.
[0046] However, when the first compound and the second compound are used together, the second compound plays a role in physically suppressing and stabilizing the aggregation of the reduced metal particles during the reduction process, so it is preferable to use the first compound and the second compound together.
[0047] In this case, the first compound and the second compound can be mixed and used in a weight ratio of 1:0.3 to 0.7. If the weight ratio of the second compound to the first compound is less than 0.3 parts by weight, it is difficult to obtain the effect of improving the yield of carbon nanotubes by the metal catalyst, and if it is used in a weight ratio exceeding 0.7 parts by weight, there is a problem that the phase stability of the colloidal solution decreases, resulting in a decrease in process efficiency and synthesis efficiency, so it is preferable to mix and use within the above weight range.
[0048] Meanwhile, the mixture preparation step may include a first mixing step of mixing and stirring a solvent, a metal salt and a surfactant, and a second mixing step of adding a reducing agent and a performance enhancer to the mixture obtained through the first mixing step and stirring the mixture.
[0049] Specifically, the first mixing step is a step of mixing a surfactant into a solvent and then mixing a metal salt, where the surfactant causes the metal salt to form micelles or reverse micelles and disperse in the solvent. In this case, if the surfactant and metal salt are simultaneously added to the solvent and mixed, the metal salt is not completely and uniformly solubilized, so in order to uniformly solubilize the metal salt, it is preferable to first mix the solvent with the surfactant and then add the metal salt.
[0050] Furthermore, if this mixing step is carried out at room temperature, the phase of the mixture becomes unstable and phase separation occurs, so in the first mixing step, mixing is preferably carried out at a temperature of 40 to 70° C. In order to form a more stable phase, it is preferable to add a surfactant to the solvent, raise the temperature, and add the metal salt while maintaining the temperature within the above range.
[0051] If the temperature is higher than the above range, the metal salt may aggregate due to evaporation of the solvent, so the temperature is preferably limited to within the above range. In this case, mixing after the addition of the metal salt may be performed for 4 to 8 hours.
[0052] The mixture obtained through the first mixing step is preferably cooled to 10 to 30° C. for a stable reaction thereafter. If the second mixing step is performed without a cooling step and the temperature of the mixture is kept high, abnormal growth of metal and the resulting problem of metal particle precipitation may occur. Therefore, the mixture obtained through the first mixing step is preferably cooled before being introduced into the second mixing step.
[0053] In this case, ultrasonic dispersion in water can be performed in the first mixing step to form metal salts of more uniform and uniform size. Ultrasonic dispersion can be performed by applying ultrasonic waves of 30 to 45 W output to the cooled mixture for 10 to 20 minutes, and if the irradiation output is outside the above range, the dispersion efficiency may decrease or the size of the metal salt may be unevenly formed.
[0054] Next, the second mixing step is a step in which a reducing agent and a performance improver are added to the mixture obtained through the first mixing step and stirred. In order to obtain the reduction effect by the reducing agent and the performance improvement effect by the performance improver, each component can be mixed and stirred for 10 to 24 hours.
[0055] When the mixture preparation step is carried out in two stages as described above, the metal salt is first uniformly dispersed in the solvent in the form of nano-sized particles through the first mixing step, and then reduced through the second mixing step, and the catalytic performance improving effect of the performance improver is uniformly imparted to each individual metal particle. Therefore, compared to the case where each of these components is mixed simultaneously to prepare an emulsion mixture, the metal microparticles can be dispersed more uniformly and stably, and the performance improving effect of the performance improver can be achieved more effectively.
[0056] Therefore, as described above, performing the dispersion and reduction of the metal salt in separate steps and adding the performance improver in the reduction step is effective in making the synthesized carbon nanotubes uniform and improving the yield.
[0057] A gas phase mixture forming step is then performed in which the emulsion mixture is mixed with a carrier gas to form a gas phase mixture.
[0058] As previously mentioned, the metal particles dispersed within the emulsion mixture of the present invention are small, on the order of nanometers in size, and therefore can form in the gas phase, either by themselves or mixed with other gases.
[0059] Specifically, the emulsion mixture can be mixed with a carrier gas and formed into a gas phase by a spray or atomization method, and the gas phase mixture thus formed into a gas phase is supplied to a reactor and used for the synthesis of carbon nanotubes. At this time, the carrier gas can be an inert gas such as argon, neon, helium, nitrogen, etc., or a hydrocarbon gas, and preferably, a characterized gas such as hydrogen or hydrogen sulfide can be supplied together with the carrier gas, but is not limited thereto.
[0060] In this step, the spray flow rate of the emulsion mixture is preferably 0.10 to 0.85 ml / min, and the flow rate of the carrier gas is preferably 30 to 450 sccm. If these supply flow rates are outside the above ranges, it may be difficult to uniformly disperse and diffuse the metal microparticles in the gas phase, resulting in problems such as a decrease in the carbon nanotube synthesis yield, an increase in the amount of unreacted catalyst, and a decrease in economic efficiency and process efficiency due to the use of excess carrier gas.
[0061] Meanwhile, in this step, a carbon source gas can be supplied together with the emulsion mixture and carrier gas, and in order to achieve effects such as improving the yield of carbon nanotubes, minimizing unreacted materials, and improving economy and productivity, it is preferable that the supply flow rate of the carbon source gas is 20 to 200 sccm.
[0062] In particular, when water is used as the solvent and a hydrocarbon gas, which is a carbon source, is not used as the carrier gas, a carbon source gas must be supplied together in the gas phase mixture formation step to form carbon nanotubes, and when a carbon-containing solvent, such as an aromatic hydrocarbon, an aliphatic hydrocarbon, or an alcohol compound, is used as the solvent, a carbon source gas may or may not be further supplied in this step.
[0063] When a carbon source gas is supplied together in the gas phase mixture forming step, the carbon source gas may be an organic compound selected from the group consisting of carbon monoxide, saturated or unsaturated aliphatic hydrocarbons having 1 to 6 carbon atoms, or aromatic hydrocarbons having 6 to 10 carbon atoms. Such a carbon source gas may contain 1 to 3 heteroatoms selected from the group consisting of oxygen, nitrogen, chlorine, fluorine, and sulfur.
[0064] According to one preferred embodiment of the present invention, characterized gases such as H2, H2S, NH3, etc. may be co-fed along with the carbon source gas.
[0065] Next, a reaction step is performed in which the gas mixture formed in the gas mixture forming step is reacted to obtain carbon nanotubes.
[0066] This step involves introducing the gas phase mixture into a heated reactor to form carbon nanotubes. In the previous step, the catalyst particles are formed into uniformly sized nanoparticles, which are then dispersed as a stable and uniform gas phase, making it possible to continuously synthesize carbon nanotubes under milder reaction conditions than in typical carbon nanotube gas phase synthesis reactions.
[0067] The temperature of the reactor for synthesizing carbon nanotubes in this step may be 600 to 1500° C. If the temperature is outside this range, there are problems such as a decrease in the selectivity of carbon nanotubes and a decrease in the production yield of carbon nanotubes due to an increase in unreacted reactants, so it is preferable to carry out the synthesis reaction within the above temperature range.
[0068] Hereinafter, specific operations and effects of the present invention will be described according to an embodiment of the present invention, however, this is presented as a preferred example of the present invention and the scope of the present invention is not limited by the embodiment.
[0069] [Production Example] First, 100 parts by weight of benzene as a solvent was mixed with 8 parts by weight of cetyltrimethylammonium bromide, and the mixture was heated to 45°C, after which 0.7 parts by weight of metal salt (FeCl3) was added and mixed for 6 hours. During mixing, 40 W ultrasonic waves were applied for 15 minutes. The mixture was then cooled to 27°C.
[0070] Next, 1.5 parts by weight of LiBH4 as a reducing agent and 0.19 parts by weight of a performance enhancer were mixed with the mixture and stirred for 8 hours to prepare an emulsion mixture. In this case, a mixture of indole and disteardimonium hectorite in a weight ratio of 1:0.5 was used as the performance enhancer.
[0071] Next, the emulsion mixture was introduced into a reactor heated to 1200°C at a rate of 0.40 ml / min, while argon (Ar) was supplied as a carrier gas at a flow rate of 100 sccm. The reaction was carried out for a total of 20 minutes to synthesize carbon nanotubes.
[0072] [Experimental Example 1] The content of the performance enhancer was changed as shown in Table 1 below to prepare emulsion mixtures, and carbon nanotubes were synthesized using each emulsion mixture in the same manner as in the preparation example, and the synthesis yield and diameter distribution of carbon nanotubes were measured, and the results are also shown in Table 1. The synthesis yield was calculated according to the following formula (1). For the diameter distribution diagram, scanning electron microscope (SEM) and transmission electron microscope (TEM) photographs of each synthesized carbon nanotube were taken, and the diameters of 10 randomly selected carbon nanotube strands, including the thinnest and thickest ones, were measured in the photographs, and the average value and standard deviation were calculated and shown in Table 1. Here, the content of the performance enhancer in Table 1 means the weight based on 100 parts by weight of benzene.
[0073] Synthesis yield (%) = [amount of carbon nanotubes produced (g) / amount of metal salt supplied (g)] × 100 Equation (1)
[0074] [Table 1]
[0075] Looking at the experimental results in Table 1, it can be seen that in Examples 1 to 4, the synthesis yield was significantly higher than in Comparative Examples 1 to 3, the standard deviation of the diameter of the obtained carbon nanotubes was less than 0.3, and the diameter of the carbon nanotubes for each strand was uniform.
[0076] Specifically, when comparing Comparative Example 1 and Comparative Example 2, it can be seen that when the content of the performance improver is insufficient, the effect of improving the synthesis yield and uniforming the diameter distribution diagram due to the performance improver does not appear. Also, in the case of Comparative Example 3, the effect of the performance improver does not appear, but this is considered to be due to the fact that the content of the performance improver is excessive, causing phase instability of the emulsion mixture.
[0077] Therefore, it was confirmed from the results of this experiment that the content of the function improver for improving the synthesis yield of carbon nanotubes and making the diameter uniform is 0.1 to 0.4 parts by weight with respect to 100 parts by weight of the solvent.
[0078] [Experimental Example 2] Using the same method as in Preparation Example, emulsion mixtures were prepared by varying the contents of indole I and disteardimonium hectorite D used as performance enhancers as shown in Table 2 below, and carbon nanotubes were synthesized using each emulsion mixture in the same manner as in Preparation Example. Then, the synthesis yield and diameter distribution were measured in the same manner as in Experimental Example 1, and the results are shown in Table 2.
[0079] [Table 2]
[0080] From the experimental results in Table 2, it can be seen that in the case of Example 5, although the synthesis yield was high, there was a problem that the diameter of the carbon nanotubes was not uniform, and in the case of Example 6, there was a problem that the synthesis yield was low. Therefore, it can be seen that it is preferable to use indole and disteardimonium hectorite in combination as a performance enhancer.
[0081] Furthermore, in the case of Example 7, even though both indole and disteardimonium hectorite were included, the same results as in Example 5 were observed, and in the case of Example 11, the same results as in Example 6 were observed. From these results, it was confirmed that when both indole and disteardimonium hectorite are used as performance enhancers, it is preferable to use them in a weight ratio of 1:0.3 to 0.7.
[0082] The present invention is not limited to the specific embodiments and explanations described above, and various modifications can be made by anyone having ordinary knowledge in the technical field to which the invention pertains without departing from the gist of the present invention as claimed in the claims, and such modifications are within the scope of protection of the present invention. [Industrial Applicability]
[0083] The method for continuously producing carbon nanotubes using a vapor phase synthesis method according to the present invention has the effect of uniformly controlling the diameter of carbon nanotubes and increasing the production yield of carbon nanotubes, and therefore has industrial applicability.
Claims
1. a liquid phase mixture forming step of mixing and stirring a solvent, a metal salt, a surfactant, a reducing agent, and a performance enhancer to produce an emulsion mixture; a gas phase mixture forming step of mixing the emulsion mixture with a carrier gas to produce a gas phase mixture; and introducing the gas phase mixture into a heated reactor to react to form carbon nanotubes. The performance enhancer includes at least one of an indole, an imidazole, and a hectorite compound; The liquid phase mixture forming step includes: A first mixing step of mixing and stirring a solvent, a metal salt, and a surfactant; A second mixing step of adding a reducing agent and a performance improver to the mixture obtained through the first mixing step and stirring the mixture; The solvent is at least one selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, and alcohol compounds, The emulsion mixture contains, relative to 100 parts by weight of a solvent, 0.01 to 5 parts by weight of a metal salt, 5 to 17 parts by weight of a surfactant, 0.02 to 10 parts by weight of a reducing agent, and 0.1 to 0.4 parts by weight of a performance improver; The performance improver is a mixture of at least one first compound selected from the group consisting of indole and imidazole, and a second compound containing a hectorite compound. A method for continuous production of carbon nanotubes.
2. 2. The method of claim 1, wherein a carbon source is further mixed in the gas phase mixture forming step.
3. a liquid phase mixture forming step of mixing and stirring a solvent, a metal salt, a surfactant, a reducing agent, and a performance enhancer to produce an emulsion mixture; a gas phase mixture forming step of mixing the emulsion mixture with a carrier gas to produce a gas phase mixture; and introducing the gas phase mixture into a heated reactor to react to form carbon nanotubes. The performance enhancer includes at least one of an indole, an imidazole, and a hectorite compound; The liquid phase mixture forming step includes: A first mixing step of mixing and stirring a solvent, a metal salt, and a surfactant; A second mixing step of adding a reducing agent and a performance improver to the mixture obtained through the first mixing step and stirring the mixture; the solvent is water; In the liquid phase mixture forming step, a carbon source is additionally mixed; The emulsion mixture contains, relative to 100 parts by weight of a solvent, 0.01 to 5 parts by weight of a metal salt, 5 to 17 parts by weight of a surfactant, 0.02 to 10 parts by weight of a reducing agent, and 0.1 to 0.4 parts by weight of a performance improver; The performance improver is a mixture of at least one first compound selected from the group consisting of indole and imidazole, and a second compound containing a hectorite compound. A method for continuous production of carbon nanotubes.
Citation Information
Patent Citations
Liquid crystal display device
JP1999109878A
Method for producing carbon nanotubes
JP2004534715A